2021
DOI: 10.1016/j.ssmph.2021.100878
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the mental health impact of the COVID-19 lockdown: Longitudinal evidence from the Netherlands

Abstract: Recent contributions highlighted gender differences in the mental health consequences of COVID-19 lockdowns. However, their cross-sectional designs cannot differentiate between pre-existing gender differences and differences induced by lockdowns. Estimating fixed-effects models using longitudinal data from the Lifelines biobank and cohort study with repeated mental health measurements throughout the lockdown, we overcome this caveat. Significant gender differences in mental health during the lockdown were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 44 publications
7
41
3
Order By: Relevance
“…Our study found that female medical students reported experiencing significantly more depressive symptoms than male students, comparable with earlier epidemiological studies (10,23). Research on the disparity between women and men during the COVID-19 pandemic revealed that female students had higher COVID-19 pandemic risk perceptions than male students (23,24). That research also estimated higher conscientiousness, neuroticism, tolerance to experiences, and tension to be higher in female university students (23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study found that female medical students reported experiencing significantly more depressive symptoms than male students, comparable with earlier epidemiological studies (10,23). Research on the disparity between women and men during the COVID-19 pandemic revealed that female students had higher COVID-19 pandemic risk perceptions than male students (23,24). That research also estimated higher conscientiousness, neuroticism, tolerance to experiences, and tension to be higher in female university students (23).…”
Section: Discussionsupporting
confidence: 88%
“…The global summation of the nine issues delineated the level of the severity of depression. Recommended cut off PHQ-9 scores for level of depression severity (12): minimal (score 0-4), mild (score 5-9), moderate (score 10-14), moderately severe (score [15][16][17][18][19], severe (score [20][21][22][23][24][25][26][27]. Patient Health Questionnaires had good internal consistency (Cronbach's Alpha = 0.77), adequate split-half reliability (r = 0.80) in our data.…”
Section: Depressive Symptoms Measurementioning
confidence: 61%
“…Mental health problems in postgraduate students are more serious during the pandemic than before the pandemic. We believe that the pandemic and lockdown measures have exacerbated the negative feelings of anxiety, depression and social anxiety among postgraduate students, as can be seen in longitudinal studies in other countries [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%
“…Considering the mental health impact due the pandemic, it was also observed that females experienced more depression symptoms after lockdown while males experienced more anxiety symptoms [ 34 ], but after a few weeks the gender-differences disappeared and both groups experienced resilience feelings [ 35 ]. The mental impact of the pandemic in LMICs varied from immediate distress and discrimination experienced mainly by healthcare workers to long-term side effects such as higher prevalence of depression and other mood disorders as a result of social isolation, job insecurity, unemployment and economic distress [ 36 ].…”
Section: Introductionmentioning
confidence: 99%